2016
DOI: 10.1016/j.tvjl.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and magnetic resonance diagnosis of variations in the anatomical location of the major salivary glands in 1680 dogs and 187 cats

Abstract: Durand, A., Finck, M., Sullivan, M., and Hammond, G. (2016) Computed tomography and magnetic resonance diagnosis of variations in the anatomical location of the major salivary glands in 1680 dogs and 187 cats. Veterinary Journal, 209, There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/118346/ OBJECTIVE:To assess the ventro 20° rostral-dorsocaudal oblique (V20R-DCdO) projection for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 30 publications
2
32
0
2
Order By: Relevance
“…In this study, the images were obtained using a high‐field MRI magnet that showed excellent visualization of the normal appearance of the salivary glands, and associated anatomical structures. Similar results have been observed in dogs using high‐field (Durand et al., ) and low‐field protocols (Kneissl & Probst, ; Weidner et al., ). The main limitations of low‐field MR imaging are the lower signal‐to‐noise ratios, poor spatial resolution, and motion artifacts (Tavernier & Cotten, ).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, the images were obtained using a high‐field MRI magnet that showed excellent visualization of the normal appearance of the salivary glands, and associated anatomical structures. Similar results have been observed in dogs using high‐field (Durand et al., ) and low‐field protocols (Kneissl & Probst, ; Weidner et al., ). The main limitations of low‐field MR imaging are the lower signal‐to‐noise ratios, poor spatial resolution, and motion artifacts (Tavernier & Cotten, ).…”
Section: Discussionsupporting
confidence: 82%
“…Exploration and clinical evaluation of the salivary glands in the dog is laborious because of their anatomical complexity, which challenges the diagnosis of morphological changes simply via physical examination. Diagnostic imaging techniques such as conventional sialography (Tadjalli, Dehgani, & Basiri, ), ultrasound (Lenoci & Ricciardi, ), CT (Durand et al., ; Kneissl et al., ), and MRI (Durand et al., ; Weidner et al., ) have been used to evaluate the salivary gland and their ducts in dogs. In some cases, radiography may be sufficient to make a diagnosis when the clinical signs and physical examination give detailed information on the disorder (Perez‐Ecija, Estepa, & Mendoza, ); however, if radiographic assessment is inconclusive, then more advanced imaging techniques are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations